Визначення дефектів трансформаторного обладнання з використанням частотних діагностичних параметрів - Рубаненко, Олександр Євгенійович; Лабзун, Михайло Павлович; Грищук, Максим Олександрович (НТУ "ХПІ", 2017)
Метою статті є дослідження пошкоджуваності силових трансформаторів, методів і засобів визначення їх технічного стану. Представлені результати досліджень пошкоджуваності силових трансформаторів, які показують, що значна частина таких пошкоджень є дефекти магнітопроводу та обмоток, відносно інших вузлів силового трансформатора. У статті звернено увагу на використання FRAnalyzer і на відсутність вітчизняної нормативної документації, що дозволяє аргументовано інтерпретувати результати діагностування таким обладнанням. Стаття дозволяє оцінити ефективність методів та засобів діагностування силового обладнання енергосистем.

The article presents the results of studies of the damageability of power transformers, which indicate that a considerable part of such damages are defects in magnetic circuits and windings. Also, studies Defects power equipment of power systems in most cases is from 1 to 3 years of operation and one after 25 years. These are such damages as radial and axial deformations of windings, sliding of coils of windings, results of "fire in steel", etc. It is also shown that among the most frequently damaged nodes and parts of a transformer, there are windings and magnets. This indicates that monitoring of the current and the idling power of the transformer, the active insulation resistance of the windings, the short-circuit resistance and other diagnostic parameters stipulated in the regulatory and passport documentation, using diagnostic tools available for enterprises operating transformers, Some defects of these parts and assemblies, especially at an early stage of their development. Determined that the defects associated with defects in the windings and magnetic deterioration best detected by comparing the frequency characteristics. Attention is also drawn to the fact that sometimes effective use of modern diagnostic equipment is limited by the absence of domestic normative documentation that allows to interpret the results of diagnosing transformers with new methods reasonably, to assess the actual technical condition that is necessary for its account during operation, repair planning, replacement and disposal.
Definition defects of transformer equipment using frequency diagnostic parameters
Keywords: силовий трансформатор; трансформаторне обладнання; частотний аналіз; магнітопровід; обмотки; ТО; power transformer; frequency analysis; magnetic core